Human Immunodeficiency Virus Type 2 (HIV-2) Gag Is Trafficked in an AP-3 and AP-5 Dependent Manner - Alford, Justine E.; Marongiu, Michela; Watkins, Gemma L.; Anderson, Emma C. (PLOS ONE, 2016)
Although human immunodeficiency virus (HIV) types 1 and 2 are closely related lentiviruses with similar replication cycles, HIV-2 infection is associated with slower progression to AIDS, a higher proportion of long term non-progressors, and lower rates of transmission than HIV-1, likely as a consequence of a lower viral load during HIV-2 infection. A mechanistic explanation for the differential viral load remains unclear but knowledge of differences in particle production between HIV-1 and HIV-2 may help to shed light on this issue. In contrast to HIV-1, little is known about the assembly of HIV-2 particles, and the trafficking of HIV-2 Gag, the structural component of the virus, within cells. We have established that HIV-2 Gag accumulates in intracellular CD63 positive compartments, from which it may be delivered or recycled to the cell surface, or degraded. HIV-2 particle release was dependent on the adaptor protein complex AP-3 and the newly identified AP-5 complex, but much less so on AP-1. In contrast, HIV-1 particle release required AP-1 and AP-3, but not AP-5. AP-2, an essential component of clathrin-mediated endocytosis, which was previously shown to be inhibitory to HIV-1 particle release, had no effect on HIV-2. The differential requirement for adaptor protein complexes confirmed that HIV-1 and HIV-2 Gag have distinct cellular trafficking pathways, and that HIV-2 particles may be more susceptible to degradation prior to release.